An Overview of Used-Products Remanufacturing - Magdalene, Andrew-Munot; Raafat, N Ibrahim; Ervina, Junaidi (Canadian Center of Science and Education, 2015)
Remanufacturing is an important production activity, which is mainly driven by the increasingly strict environmental regulations imposed by governmental bodies, growing customers' awareness of green environment and potential economic benefits of remanufacturing. In this paper, the key motivating factors for companies to engage in remanufacturing program are examined. The major sources for acquiring used-products and the subsequent markets for selling remanufactured products are also examined. More importantly, the generic-key remanufacturing processes are examined and the corresponding unique characteristics are highlighted. Four examples of remanufacturing process of different products are presented to demonstrate that exact number and sequence of remanufacturing process largely depended on the type of product being remanufactured. In sum, this paper presents an overview of used-products remanufacturing, which in many ways would benefit the general public, environment, manufacturers/remanufacturers, as well as researchers.